Ancient Hawaiian house lots and their flora: a review of Great Māhele plant claims with a special focus on Pritchardia (loulu) palms - Brien A. Meilleur (Revue d'ethnoécologie)
A review of Foreign Testimony records of the Native Register from the mid-19th century Hawaiian land division program known as the Great Māhele (~1846-1854) has led to a better understanding of ancient Hawaiian house lot plantings. While a great deal is known about the management and use of indigenous, endemic and Polynesian-introduced plants and their distribution within wild and domesticated Hawaiian landscapes, the floristic composition of the plants cultivated close to residences is poorly documented. This is true for the period immediately after Western contact (1778) and for the decades following the arrival of American and European missionaries in the 1820s and 1830s, and indeed for the 19th century generally. The results of this review are presented here, with those plants claimed in the Native Register and those explicitly claimed near dwellings identified and described. Perhaps the most remarkable finding is the prominence of endemic Pritchardia (loulu) palms grown near mid-19th century Hawaiian residences, not only in terms of the number of claims made for loulu (63) and the actual number of individual loulu plants claimed (272), but also their distribution within the Hawaiian archipelago. Hypotheses are offered to account for these patterns. The value of using archival materials and ancient texts in ethnobiological research is underlined.